PROBLEMATIKA PENERAPAN KURIKULUM 2013 PADA PEMBELAJARAN LINTAS MINAT KIMIA DI KELAS XI ILMU-ILMU SOSIAL (IIS) - Nora Darmayanti; Rosa Murwindra; Dwi Putri Musdansi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
This research aims to know what are the problematics of the implementasion curriculum 2013 of chemical interest learning in class XI Social Sciences (IIS) of SMA Negeri 1 Kuantan Hilir Seberang. The research subjects were the Headmaster or Headmaster proxy in the field of curriculum, one chemistry teacher and students of class XI Social Sciences (IIS). This research is kind of qualitative research the using data collection techniques by observation, interview, and documentation. Data analysis techniques which used are data reduction, data display and conclusion drawing.Whereas the validity and reliability tests use the credibility, Dependability, and confirmability tests. Based on the results of the research, it can be concluded from the problematics of the implementasion curriculum 2013 of chemical interest learning in class XI Social Sciences (IIS) of SMA Negeri 1 Kuantan Hilir Seberang, that are : The first, at the planning stage the teacher is constrained in realizing the learning device because of the allocation of time and conditions of students. The second, in the learning process that occurs because the method is less varied and difficult to apply scientific and limited facilities and infrastructure. The third, evaluations or assessments in the 2013 curriculum that have not been able to be applied.